PARTNER SCHOOLS EVALUATION OF PRE-SERVICE TEACHERS PERFORMANCE DURING FIELD PRACTICE: A CASE STUDY FROM FKIP UMMY SOLOK - Hana Adhia; Risza Dwiputri; Helvita Roza; Ikhwan; Redo Andi Marta; Roza Zaimil (ELP (Journal of English Language Pedagogy), 2026)
This study examines the performance evaluation of Field Practice (PLK) students from the Faculty of Teacher Training and Education (FKIP) UMMY Solok in 2025 based on assessments from partner schools. The research employed a descriptive quantitative method, collecting data through structured questionnaires distributed to supervising teachers at partner schools. Six key competency areas were assessed: professional ethics, communication skills, technology integration, teamwork and collegial collaboration, self-development and reflective practice, and teaching competence. The results indicate that PLK students demonstrated strong performance across all evaluated dimensions, with 100% of respondents rating teamwork and collegial collaboration, self-development and reflective practice, and teaching competence as "Good", while ethics and technology integration received 75% "Good" ratings and communication skills achieved 50% "Very Good" and 50% "Good" ratings. No "Sufficient" or "Poor" ratings were recorded in any category. These findings suggest that the PLK program at FKIP UMMY Solok effectively prepares pre-service teachers with essential competencies required in school settings, though continuous improvement in ethics and technology integration remains necessary.